Understanding Trauma Bonding through Saussurian Semiotics in Hozier's Cherry Wine - Octaviyanti, Adhillah Pratiwi; Sakinah, R. Myrna Nur (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
This research examines the representation of trauma bonding in Hozier's song "Cherry Wine" using Ferdinand de Saussure's semiotic approach. Trauma bonding refers to the emotional attachment that develops between a victim and their abuser in an abusive relationship. The purpose of this study is to analyze how the lyrics of the song reflect the complexities of such relationships, focusing on the dynamic of love and violence that traps victims emotionally. A qualitative descriptive method was employed, with data collected through an in-depth analysis of the song lyrics. The lyrics serve as the signifier, while the emotional experiences depicted represent the signified. The research findings reveal that Hozier portrays the victim’s conflicting emotions—simultaneous love and pain—through contrasting imagery, such as warmth and coldness, highlighting the unpredictable nature of abuse. This study contributes to a broader understanding of how popular music can be used to raise awareness about social issues, particularly domestic violence. In conclusion, the analysis demonstrates that "Cherry Wine" effectively conveys the emotional complexities of trauma bonding, providing listeners with insight into the experiences of victims.